THE METHOD OF CALCULATING CHARACTERISTICS OF A STABILIZING LAYER - Bondarenko, I. O. (Science and Transport Progress, 2007)
For the purpose of considering the issues of safeguarding the conditions of strength, stability and susceptibility to deformations, there has been introduced a concept of stabilizing layer. Depending on the requirements to track susceptibility to deformations, recommendations have been developed for calculating the parameters of stabilizing layer.